Running at Increasing Intensities in the Heat Induces Transient Gut Perturbations - Wallett, A. M.; Etxebarria, N.; Beard, N. A.; Saunders, P. U.; Welvaert, M.; Périard, J. D.; McKune, A. J; Pyne, D. B. (International Journal of Sports Physiology and Performance, 2021)
Purpose: The risk of exercise-induced endotoxemia is increased in the heat and is primarily attributable to changes in gut permeability resulting in the translocation of lipopolysaccharides (LPS) into the circulation. The purpose of this study was to quantify the acute changes in gut permeability and LPS translocation during submaximal continuous and high-intensity interval exercise under heat stress.